Disruption of nigrostriatal and cerebellothalamic pathways in dopamine responsive Holmes' tremor. Issue 8 (1st May 2008) - Seidel, S; Kasprian, G; Leutmezer, F; Prayer, D; Auff, E
Abstract : Holmes' tremor is an unusual combination of rest, postural and kinetic tremor of the extremities. Medical treatment of this condition still remains unsatisfactory. The case of a 20-year-old female patient is reported who developed right-sided Holmes' tremor 9 months after a left-sided, cavernoma induced midbrain/pontine haemorrhage at the age of 16 years. Beta-CIT single photon emission computed tomography revealed abolished dopamine transporter activity in the left basal ganglia and striatum, in accordance with missing ipsilateral tegmento-frontal connectivity (medial forebrain bundle), demonstrated by diffusion tensor MRI. Tractography showed reduced fibre connectivity of the superior and middle cerebellar peduncles on the lesioned side. Administration of pramipexole and L-DOPA led to a clinically significant reduction in tremor severity. In conclusion, our results support the notion that Holmes' tremor was a result of diminished striatal dopaminergic input in our patient.